SAGE visual methods - Hughes, Jason (SAGE library of research methods, 2012)
In contemporary Western societies, the visual domain has come to assume a hitherto unprecedented cultural centrality. The visual has become imbued with a symbolic potency, a signifying power that seemingly eclipses that of all other sensory data. The central aim of this four-volume collection is to explore key approaches to visual research methods and to consider some of the core principles, issues, debates and controversies surrounding the use of visual techniques in relation to three key enterprises: 1. documentation and representation; 2. interpretation and classification and 3. elicitation and collaboration.